Investment and Growth in the Middle East and North Africa - Bisat, Amer.; El-Erian, Mohamed; El-Gamal, Mahmoud; Mongelli, Francesco (Washington, D.C. : International Monetary Fund, 1996)
The paper considers investment and growth in the Middle East and North Africa (MENA) region. Notwithstanding cross-country differences, investment as a whole has been too low, too heavily tilted toward the public sector, too highly dependent on external influences, and less productive than in many other regions. Improving the region's investment performance is critical if policymakers are to succeed in increasing the region's economic growth rate. After discussing the relationship between investment and growth, the paper analyzes the investment responsiveness of various countries in the region and notes the policy priorities for strengthening the basis for rapid and sustained economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet